Community-Based Social Welfare: A Sociological Study of Local Community Organizing - Al Qhuraissy, Muammar Akbar (Socious Journal, 2025)
Persistent local social welfare problems indicate the limitations of state-centered welfare approaches in addressing micro-level social dynamics and community-specific needs. This condition has encouraged the emergence of community-based social welfare practices through local community organizing as an adaptive response to the shortcomings of formal interventions. This study aims to analyze how local community organizing processes shape, sustain, and constrain community-based social welfare from a sociological perspective. The study employs a qualitative approach with a sociological design, utilizing in-depth interviews, participant observation, and community document analysis. The findings reveal that community-based social welfare is a social construction produced through the interaction of organizational structures, power relations, and internal social capital. Community organizing functions as a mechanism for building solidarity and collective capacity, while simultaneously creating arenas of contestation that affect the inclusiveness of welfare access. Furthermore, external interventions and social change significantly influence the sustainability of community-based welfare, particularly in relation to community autonomy and social legitimacy. This study highlights the importance of positioning communities as primary actors in sustainable social welfare practices and policies.